Características clínico patológicas asociadas a fallecimiento por Covid-19 en pacientes atendidos en cuidados intensivos Hospital Regional de Loreto 2020 - Rios Icomena, Dany Narita (2024)
The objective was to determine the association that exists between the clinical pathological characteristics and death from COVID -19 in people treated in Intensive Care in 2020 at the Regional Hospital of Loreto Iquitos 2023. The method was quantitative, non-experimental design, descriptive, correlational, retrospective. The population and sample were made up of 180 medical records of patients with COVID - 19. The technique was documentary review and the instruments, Clinical Pathological Characteristics Record Sheet of patients with COVID - 19 and Death Record Sheet. of the patient due to COVID-19. The statistical package SPSS version 24.0 was used and the chi[1]square statistical test (x^2) the bivariate analysis. The results obtained were: 52.2% were 60 years of age or older, 72.2% were men, 56.1% did not suffer from diabetes, 58.3% suffered from arterial hypertension, 84.4% did not suffer from obesity, 82.2% did not suffer from kidney disease, 100% did not suffer from cancer, 78.9% presented a severe level of oxygen saturation (less than 92%), 74.4% received invasive mechanical ventilation (intubation), 100% received antibiotic therapy, 46.7% had an illness time of 1 to 3 days, 66.1% had a stay in the ICU of less than 7 days and 96 1% died from COVID 19. In conclusion, there is a statistical association with age p = 0.000, sex p = 0.009, diabetes p = 0.017, arterial hypertension p = 0.016, obesity p = 0.002, oxygen saturation level p = 0.001, illness time p= 0.033, and length of stay in the ICU p= 0.026.